Notas sobre algunas orquidáceas de colombia (1941)
Malaxis quadrata L. / Catasetum barbatum Lindl. / Acacallis cyanea Lindl. / Maxillaria miniata / Maxillaria nívea / Maxillaria aurea / OLIVERIANA Reichb. / Odontoglossum megalophium / Pachyphyllum Schultesii L.